2016
DOI: 10.1371/journal.pone.0165242
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Outcome and Risk Factors of Intensive Care Unit Infections in the Lagos University Teaching Hospital (LUTH), Lagos, Nigeria

Abstract: BackgroundInfections are common complications in critically ill patients with associated significant morbidity and mortality.AimThis study determined the prevalence, risk factors, clinical outcome and microbiological profile of hospital-acquired infections in the intensive care unit of a Nigerian tertiary hospital.Materials and MethodsThis was a prospective cohort study, patients were recruited and followed up between September 2011 and July 2012 until they were either discharged from the ICU or died. Antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…WHO reports estimate approximately 30% of ICU patients are affected by at healthcare-associated infections while incidence is 3-fold higher in low and middle-income countries [18]. Several reports from these countries suggest the lack of surveillance data thus having a negative influence on the implementation of preventive measures [19][20][21][22][23]. Two EPIC studies in a span of 10 years have demonstrated 20% increase in prevalence of ICU-acquired infections [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…WHO reports estimate approximately 30% of ICU patients are affected by at healthcare-associated infections while incidence is 3-fold higher in low and middle-income countries [18]. Several reports from these countries suggest the lack of surveillance data thus having a negative influence on the implementation of preventive measures [19][20][21][22][23]. Two EPIC studies in a span of 10 years have demonstrated 20% increase in prevalence of ICU-acquired infections [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…6 A recently published World Health Organization (WHO) review showed that "in low-and middle-income countries, the frequency of ICU-acquired infection is at least 2-3 times higher than in high-income countries; device-associated infection densities are up to 13 times higher than in the USA". 7 Critically ill patients with severe sepsis in intensive care units (ICUs) require lengthy and expensive management, with an associated high mortality, with rates ranging from 30% to 50%. 7 Graft versus host disease (GVHD) occurs in 20% to 70% of bone marrow transplant(BMT) recipients receiving grafts from different donor sources and are associated with bacteremia.…”
Section: Burden Of Infection In Critical Areasmentioning
confidence: 99%
“…7 Critically ill patients with severe sepsis in intensive care units (ICUs) require lengthy and expensive management, with an associated high mortality, with rates ranging from 30% to 50%. 7 Graft versus host disease (GVHD) occurs in 20% to 70% of bone marrow transplant(BMT) recipients receiving grafts from different donor sources and are associated with bacteremia. 8 This study includes discussions on a variety of common clinical-microbiological problems faced in the critical areas and detection of their etiological agents and resistance patterns by conventional and molecular methods.…”
Section: Burden Of Infection In Critical Areasmentioning
confidence: 99%
“…In a neonatal septicemia study involving 202 infants with risk factors for clinical features of septicemia in the first 3 days of life, 12.5% culture were positive with the predominant organisms being S. aureus (52%) and 30.7% being MRSA [25]. In intensive care unit of a Nigerian hospital, out of 71 patients with healthcare-associated infection, bloodstream and urinary tract infections were the commonest infections, and S. aureus was the commonest cause of bloodstream infection with 80% of the S. aureus being MRSA [26]. In surgical site infections for 103 patients with orthopedic surgery in a hospital in Port Harcourt, Nigeria, the commonest pathogen was S. aureus (34%) including 15 patients with MRSA [27].…”
Section: Mrsa Prevalence In Africamentioning
confidence: 99%